1971
DOI: 10.1002/pssa.2210080206
|View full text |Cite
|
Sign up to set email alerts
|

Change in creep mechanism of B.C.C. metals at transition from low to high temperatures

Abstract: The creep behaviour of Cu, Al, and Pb has been studied in a wide range of temperatures and stresses. A change both in dislocation structure and creep characteristics has been found which indicates the change in creep mechanism as the temperature rises and the applied stress decreases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…At a temperature of 673 K, in the low-stress range, their observations correspond to an activation volume of 9.7 × 10 −28 m 3 or 82 atomic volumes, smaller than that of Andrade's observations, but still large. The re-plotting by Siethoff and Ahlborn [10] of the observations of Myshlyaev et al [11] similarly shows two (or possibly three) regions of exponential dependence.…”
Section: The Activation Volumementioning
confidence: 79%
See 1 more Smart Citation
“…At a temperature of 673 K, in the low-stress range, their observations correspond to an activation volume of 9.7 × 10 −28 m 3 or 82 atomic volumes, smaller than that of Andrade's observations, but still large. The re-plotting by Siethoff and Ahlborn [10] of the observations of Myshlyaev et al [11] similarly shows two (or possibly three) regions of exponential dependence.…”
Section: The Activation Volumementioning
confidence: 79%
“…Moreover, the results of different observations do not seem to be compatible. Andrade [12] found an exponential dependence of creep rate on stress for polycrystalline copper in the stress range 5-11 MPa at 683 K while Myshlyaev et al [11] found a clear power-law dependence of the creep rate for polycrystalline copper at 673 K in the same stress range. If in fact the regimes of power-law creep and power-law breakdown are physically distinct, it is not clear to which of these regions the observations of the Andrade group refer.…”
Section: The Evidence From Metallographymentioning
confidence: 99%
“…During tension deformation, the potential barrier height U signifi cantly exceeds the potential barrier height V corre sponding to torsional deformation. For example, in the case of aluminum, U = 2.2-2.3 eV [6][7][8][9] and V = 1.2 eV [10]. The barrier U corresponds to dislocation intersection with the formation of interstitial defects [5], while the physical meaning of the barrier V Note: Here and in Table 2, i and v mean interstitial and vacancy thresholds, k and p are fractions of formed interstitial and vacancy thresholds, respectively.…”
Section: Intersection Of Screw Dislocations In Fccmentioning
confidence: 98%
“…Three different regimes may be distinguished. Regime I11 occurring at high stresses and extending at least down to room temperature [8] has been interpreted by a cross-slip mechanism [9]. I) Am Hubland, W-8700 Wurzburg, FRG.…”
Section: Introductionmentioning
confidence: 99%